SURVEI MANAJEMEN ARUNG JERAM DI SERAYU ADVENTURE INDONESIA KABUPATEN BANJARNEGARA TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
The background of this research is, Serayu Adventure Indonesia is a rafting operator who first stood inBanjarnegara district, Central Java, officially licensed from FAJI, as well as having a professional guide-guide.Masalahan focus in this study: 1) How program planning activities Rafting Adventure in Indonesia SerayuBanjarnegara? 2) How perngorganisasian people who handle whitewater rafting in Indonesia AdventureSerayu Banjarnegara? 3) What is the direction of the implementation of the program activities RaftingAdventure in Indonesia Serayu Banjarnegara? 4) How to supervise the implementation of program activitiesrafting in Indonesia Adventure Serayu Banjarnegara? This study uses a qualitative descriptive approach. Thisresearch sites in Serayu Adventure Indonesia, Banjarnegara district. Objectives of this research are, Manager,Treasurer, Person-technical person in the field, Guest, and rafting instructor. Data collection methods are used,namely, observation, interviews, and documentation. The results of this study are, 1) Serayu AdventureIndonesia already have a clear plan of work program in accordance with its vision and mission. 2) InIndonesia Adventure keorganisasiannya Serayu management has setrutur organization and a clear division oftasks. 3) The process of directing in management Serayu Adventure Indonesia implemented directly by amanager. 4) Monitoring systems management activities Serayu Adventure Indonesia made in accordance withthe steps of the research process is pengendalian.Simpulan, 1) Planning made by management SerayuAdventure Indonesia goes according to the stages of the planning process, 2) Organizing conducted byAdventure Indonesia Serayu management run in accordance with organizational basics, 3) processmanagement directives are carried out Serayu Adventure Indonesia made directly by a manager or head, 4)Monitoring conducted by the management Serayu Adventure Indonesia run in accordance with the processcontrol measures . The suggestions are: 1) Making programs more creative and add a vehicle of interest, 2) Headds so much ease vice chairman of a manager's performance. 3) to facilitate operational ditambahnyapengarungan.4 boat) rides ditambahnya children untul attract more visitors.